Personalised Fractional-Order Autotuner for the Maintenance Phase of Anaesthesia Using Sine-Tests - Marcian D. Mihai; Isabela R. Birs; Nicoleta E. Badau; Erwin T. Hegedus; Amani Ynineb; Cristina I. Muresan (Fractal and Fractional)
The research field of clinical practice has experienced a substantial increase in the integration of information technology and control engineering, which includes the management of medication administration for general anaesthesia. The invasive nature of input signals is the reason why autotuning methods are not widely used in this research field. This study proposes a non-invasive method using small-amplitude sine tests to estimate patient parameters, which allows the design of a personalised controller using an autotuning principle. The primary objective is to regulate the Bispectral Index through the administration of Propofol during the maintenance phase of anaesthesia, using a personalised fractional-order PID. This work aims to demonstrate the effectiveness of personalised control, which is facilitated by the proposed sine-based method. The closed-loop simulation results demonstrate the efficiency of the proposed approach.